Agricultural outsourcing: A comparison between the Netherlands and Japan - Igata, Masayo; Hendriksen , Astrid; Heijman, Wim (Applied Studies in Agribusiness and Commerce, 2008)
Outsourcing may well be a tool for increasing the efficiency of Japanese agriculture. However, outsourcing is not frequently used by Japanese farmers in their day-to-day management. This has resulted in a weakly developed market for agricultural contracting services. In order to take a closer look at the reasons for making use of outsourcing, a comparative study was carried out between the agricultural contracting sector in Japan and that in the Netherlands, where agricultural outsourcing is a regular practice. In the Netherlands, especially small, diversified farms that lack sufficient labour tend to outsource agricultural work; in Japan, the situation is far less clear. Cultural factors possibly play an important role.